Immature morphology of adult-born granule cells alters responsiveness and excitability in a multi-compartmental conductance-based model - Bahar Sert; Pinar Oz (The European Chemistry and Biotechnology Journal, 2025)
The dentate gyrus of the hippocampus is emerging as a focal target in pattern separation and completion in recent years. Adult neurogenesis in the subgranular zone further provides a unique developmental advantage to this region by supporting the regional activity of newborn granule cells, when required. The contribution of adult-born granule cells (AdB GCs) to the local circuits can be attributed to their differences from embryonic-born mature GCs in terms of their morphological and biophysical characteristics. AdB GCs are highly excitable cells that show sparse activity. In this study, our focus was on how the morphological distinction of early AdB GCs from mature GCs affects their responsiveness. The reduced multi-compartmental conductance-based models are designed on Python environment with Brian2 module with simple Hodgkin-Huxley type Na and K conductances. Our results indicate that the early morphology of AdB GCs is optimized for faster action potential kinetics and higher excitability compared to mature GCs, even without any biophysical differences.